Mandatory Nonfinancial Disclosure and Its Consequences on the Sustainability Reporting Quality of Italian and German Companies - Mion, Giorgio; Loza Adaui, Cristian Rolando (Sustainability, 2019)
Companies disclosing nonfinancial information through sustainability reporting practices provide markets with data on their social, environmental, and governance performance. The quality of sustainability reporting is much discussed in the literature because this quality affects factors such as the credibility of accountability and building stakeholders' trust in the company. Nonetheless, the concept of quality is multidimensional, and empirical evidence relating to the quality of sustainability reporting presents different findings. Regulations on mandatory nonfinancial disclosure (NFD) open new perspectives for research on sustainability reporting quality (SRQ). This study explored the effect of introducing mandatory NFD on SRQ by focusing on the effects of new legislation (Directive 2014/95/EU) introduced in Italy and Germany. The analysis was conducted through qualitative content analysis of the sustainability reporting practices of Italian and German companies in the top lists of stock exchanges. Sustainability reporting practices of one year before (2016) and one year after (2017) the implementation of Directive 2014/95/EU were compared. The results of 132 observations demonstrated that the quality of sustainability reporting increased after implementation of the law on mandatory NFD. Further, the effect of the law seemed to reduce the differences in SRQ of the two countries before the introduction of mandatory NFD. The results suggested that obligatoriness of NFD affects SRQ together with other relevant determinants focused on by previous research (e.g., company size and industry type).
Keywords: CSR reporting; Mandatory reporting; Nonfinancial disclosure; Sustainability reporting; Sustainability reporting quality